Instructional Packages Geography Based on Ecosystem (PIGeoEk) Development in Improving Students’ Knowledge About Ecosystem Concepts and Relation to Students’ Environmental Behavior - Ning Setianti (Universitas Negeri Jakarta, 2018)
The learning have been tended to put more emphasis on knowledge transfer. One of the efforts in improving students' knowledge about the concepts of ecosystem and relation to students’ environmental behavior is integrating Geography and environmental education developing instructional packages based on ecosystem for teachers of Geography. This study aims to develop an instructional packages geography based on ecosystem (PIGeoEk) in improving students' knowledge of the concepts of the ecosystem and related to students’ environmental behavior. A research and development (R & D) based on Borg and Gall (2007), refering to the Dick and Carey design (2009), steps has been applied by involving 80 students of grade XI majoring in social sciences of SMAN 5 Depok for treatment, and grade XI majoring in social sciences of SMAN 3 Depok as a control group. There are four instructional packages geography based on ecosystem (PIGeoEk) have been developed and instrument test used for measuring knowledge about the concepts of ecosystem and relation to students’ environmental behavior. The are four t-test have been applied to verify the effectiveness of Instructional Pakages. Research results indicate that there is a significant difference between mean of gain score obtained from post and pre test at treatment group compare to control group. Therefore, the instructional packages geography based on ecosystem (PIGeoEk) could be implemented in enhancing students' knowledge about the concepts of the ecosystem in relation to students’ environmental behavior effectively.